From the Top Down: The Practice of Macro-Appraisal - Bailey, Catherine A. (Archivaria, 1997)
This article examines the application of the macro-appraisal model, which has been practised at the National Archives of Canada since 1991. After a conceptual review of the theory behind documentation strategy and the macro-appraisal model, the article outlines the National Archives’ "planned approach" to the macro-appraisal of records of the Canadian federal government. Through a detailed analysis of four appraisals in the field of health and social welfare, a number of strengths and weaknesses of the macro-appraisal model are discussed. RÉSUMÉ Cet article traite du modèle de tri à grande échelle utilisé aux Archives nationales du Canada depuis 1991. Après un examen des concepts de la théorie supportant la stratégie documentaire et le modèle de tri archivistique à grande échelle, l’article présente l’approche planifiée des Archives nationales pour trier à grande échelle les archives du Gouvernement du Canada. Les forces et faiblesses du modèle sont discutées à l’aide d’une analyse détaillée de quatre projets de tri à grande échelle réalisées dans le domaine de la santé et des services sociaux.